2020
DOI: 10.30564/jgr.v2i3.2142
|View full text |Cite
|
Sign up to set email alerts
|

Re-examination of Hydrochemistry and Groundwater Potentials of Cross River and Imo-Kwa-Ibo Intersecting Tropical Basins of SouthSouth Nigeria

Abstract: This review attempted a detailed description of geological and hydrogeological configurations of Cross River and Imo-Akwa Ibo basins. It presented a synthesis of hydrochemistry and a description of the hydrogeological configurations of the two basins. Hydrogeologically, most areas under Cross River and  Imo-Kwa-Ibo are poor in terms of groundwater potentials. Based on the hydrochemistry, the basins hold water of excellent quality.  Groundwater sources fall in soft to moderately hard classes. The entire sources… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 127 publications
0
6
0
Order By: Relevance
“…Results from these studies showed that HCO 3 ranged from 0 to 300.8 mg/l with an average value of 23.50 mg/l (Figure 11a). Bicarbonate is typically assumed to enter the groundwater system due to the uptake of CO 2 either from soil zone gases or direct atmospheric inputs [27][28][29][31][32][33]. Additional sources can come from carbonate dissolution.…”
Section: Anion Chemistrymentioning
confidence: 99%
“…Results from these studies showed that HCO 3 ranged from 0 to 300.8 mg/l with an average value of 23.50 mg/l (Figure 11a). Bicarbonate is typically assumed to enter the groundwater system due to the uptake of CO 2 either from soil zone gases or direct atmospheric inputs [27][28][29][31][32][33]. Additional sources can come from carbonate dissolution.…”
Section: Anion Chemistrymentioning
confidence: 99%
“…Results from these studies showed that HCO3 ranged from 0 to 300.8 mg/l with an average value of 23.50 mg/l (Figure 11a). Bicarbonate is typically assumed to enter the groundwater system due to the uptake of CO2 either from soil zone gases or direct atmospheric inputs [27][28][29][31][32][33]. Additional sources can come from carbonate dissolution.…”
Section: B Cation Chemistrymentioning
confidence: 99%
“…The hydrochemistry of Groundwater is the consequential of all the reactions and processes that operate in the water from right from the condensation in the atmosphere to the time is precipitated and collected by rivers and streams, recharged into aquifers and discharged by a well [15,[19][20][21][22]. Therefore, the critical insights about aquifers' geological history and its suitability for different uses can be revealed by the groundwater chemistry [15,[23][24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…The assessment of groundwater is an essential activity for rural and urban water management, particularly in semi-arid regions, [1][2][3][4] because the ionic composition of water has a significant influence on human health. [5][6][7] Using low-quality groundwater for drinking and irrigation affects human health and plant growth and contaminates soil, making it less suitable for agriculture and household uses. Shallow groundwater is the primary source of potable water and is commonly used for household and irrigation uses in rural Nigeria, 8,9 particularly in the semi-arid northern areas of Nigeria.…”
Section: Introductionmentioning
confidence: 99%